Kardiomyopathie bei einem 22-Jährigen mit langjährigem Methamphetaminkonsum - Schwab, Dominic Mathias; Katus, Hugo; Raake, Philip (Der Internist, 2019)
This article presents the case of a 22-year-old male patient with cardiomyopathy associated with a long history of methamphetamine abuse. Echocardiography revealed a dilated cardiomyopathy with highly reduced systolic pump function and severe mitral valve regurgitation. Inotropic treatment and MitraClip® (Abbott Vascular, Santa Clara, CA, USA) implantation resulted in enhancement of hemodynamics. The rising prevalence of methamphetamine abuse should give reason to raise awareness for the diagnostic work-up and patient history particularly in cases of unexplained cardiomyopathy in young patients.